2017
DOI: 10.1097/ogx.0000000000000494
|View full text |Cite
|
Sign up to set email alerts
|

Association of Gestational Weight Gain With Maternal and Infant Outcomes: A Systematic Review and Meta-analysis

Abstract: (Abstracted from JAMA 2017;317(21):2207–2225) Gestational weight gain (GWG) in excess of Institute of Medicine (IOM) guidelines has been associated with adverse pregnancy outcomes including preeclampsia, postpartum weight retention, and offspring obesity. Prevalence of obesity and excess GWG are becoming more prevalent from 40% in 2013 to 2014, with more than 50% of obese pregnant women gaining gestational weight greater than IOM GWG recommendations in a US study from 2002 to 2008.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
60
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 0 publications
7
60
0
5
Order By: Relevance
“…This means that the parameters describing the "maternal metabolic status" remain a signi cant risk factor for adverse maternal-foetal outcomes when effective treatment eliminates the risk associated with hyperglycaemia in pregnancy. [49]. Similar results were found in the work of Papazian et al [50].…”
Section: Discussionsupporting
confidence: 89%
“…This means that the parameters describing the "maternal metabolic status" remain a signi cant risk factor for adverse maternal-foetal outcomes when effective treatment eliminates the risk associated with hyperglycaemia in pregnancy. [49]. Similar results were found in the work of Papazian et al [50].…”
Section: Discussionsupporting
confidence: 89%
“…Nearly three-quarters (70%) of women in the United States do not achieve GWG within IOM recommendations (Goldstein et al, 2017). For example, women with overweight or obesity before pregnancy are more likely to have excessive GWG than women who have a BMI in the normal range (Deputy, Sharma, Kim, & Hinkle, 2015).…”
mentioning
confidence: 99%
“…On the other hand, women who gain weight below the recommendations are more likely to have small-for-gestational age children (50,52,53) , and EPACI results were in line with (36) . The sample was % weighted.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies showed that excessive weight gain during pregnancy is associated with several adverse pregnancy outcomes, such as large-for-gestational-age births, childhood OW and OB and maternal postpartum weight retention (17,51,52) . In the EPACI study, there was not a significant different trajectory in the zBMI of children whose mothers gained excessive weight during pregnancy, when comparing with offspring of women with adequate GWG.…”
Section: Discussionmentioning
confidence: 99%